SUCROSE IN INFECTED WOUNDS: A SCIENTIFIC BASIS AND SPECULATIONS - Gabriela Oliver Rossi; Danielle Bezerra Cabral; Danielle Bezerra Cabral; Denise de Andrade (Universidade Federal do Ceará, 2013)
Sucrose use in wound treatment is a common practice that seems to promote tissue healing and reduce microbial load. The objective here was thus to analyze the scientific evidence through an integrative review to determinate indications and contraindications for use of sucrose in the form of granulated, brown (unrefined muscovado sugar) and/or refined sugar in infected wounds and thus assist the professional in clinical decision-making. Ten studies published in full articles were selected, from the period 2002 to 2012 and indexed in the PubMed, Cinahl, Lilacs and Cochrane databases. Considering the analysis of studies, mostly experimental in the animal model, sugar's effectiveness in tissue repair was verified, as was positive modulation in the inflammatory response. To elucidate the mechanisms or action of sucrose in the wound, further clinical trials are recommended in order to standardize the concentration, volume and frequency of sucrose in changes of wound dressings.